The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/liv.14621
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and ongoing trials in transplant oncology

Abstract: More than half a century has passed since the first successful liver transplantation (LT) by Thomas Starzl and this groundbreaking therapy has now become an established treatment for various indications. 1 This is reflected by more than 8000 LT performed in 2018 in the US alone and a 5-year post-transplant survival exceeding 75%. 2 Most transplants are still performed for end-stage liver failure. However, the proportion of LT performed for oncological indications is constantly rising and cancer now represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…In patients fulfilling the Milan criteria, the upper limit of the tumor number is only 3, indicating that patients with 4 or more tumors are not recommended as LT candidates. In the last two decades, numerous studies have attempted to expand the Milan criteria, and successful outcomes have been achieved [ 16 ]. Although several systems of criteria include patients with more than 3 tumor nodules, no study has compared or validated the value of these selection systems in this subpopulation of HCC patients, i.e., those who have more than 3 tumor nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In patients fulfilling the Milan criteria, the upper limit of the tumor number is only 3, indicating that patients with 4 or more tumors are not recommended as LT candidates. In the last two decades, numerous studies have attempted to expand the Milan criteria, and successful outcomes have been achieved [ 16 ]. Although several systems of criteria include patients with more than 3 tumor nodules, no study has compared or validated the value of these selection systems in this subpopulation of HCC patients, i.e., those who have more than 3 tumor nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The indications are for 1) patients with liver cirrhosis who cannot be resected due to decreased liver function, 2) patients who have been shown to have IHCCC by liver biopsy, 3) a single tumor of size 2 cm or less, and 4) have neither vascular invasion nor intrahepatic lesion on the image. 12 The upper limit of tumor markers was also set to 100 ng/mL for CA19-9. The primary outcome was the 5-year OS, and the results after a few years are awaited.…”
Section: Unresectable Ihccc Due To Poor Liver Functionmentioning
confidence: 99%
“…A Phase 2 study is currently underway to assess whether the prognosis after LT for single IHCCC of 2 cm or less associated with cirrhosis is really good. The indications are for 1) patients with liver cirrhosis who cannot be resected due to decreased liver function, 2) patients who have been shown to have IHCCC by liver biopsy, 3) a single tumor of size 2 cm or less, and 4) have neither vascular invasion nor intrahepatic lesion on the image 12 . The upper limit of tumor markers was also set to 100 ng/mL for CA19‐9.…”
Section: Lt For Intrahepatic Cholangiocellar Carcinoma (Ihccc)mentioning
confidence: 99%
“…Recently, a prospective study including patients with suspicious biliary strictures (n = 68) showed that the mutational analysis of bile cell-free DNA (cfDNA) by next-generation sequencing (NGS) in bile showed a sensitivity and specificity of 96.4% and 69.2%, respectively. More interestingly, 22 out of 35 patients initially categorized as having a benign/indeterminate stricture were finally diagnosed of malignancy during the follow-up and in them, the NGS assay showed a 100% sensitivity for malignancy diagnosis [59] . Validation studies including patients with PSC are eagerly awaited.…”
Section: Future Perspectivesmentioning
confidence: 99%